Dziecięca choroba „lewizny” w światopoglądzie muzyków lwowskich w latach 1920–1930 - Kijanowska-Kamińska, Luba (Musica Galiciana. Kultura muzyczna Galicji w kontekście stosunków polsko-ukraińskich, 2023)
The article outlines one aspect of the attitude to socialism in the artistic circles of Lviv and Galicia, which has so far remained on the margins, the leftist views of the outstanding musicians of that period in the Galician country, their causes and consequences. Several social and political circumstances contributed to the adoration of the leftist views of the Galician intelligentsia, both Polish and Ukrainian. One of them – influences coming from the former capital of the Habsburg Empire of Vienna, at that time not accidentally called “Red Vienna”. The second reason for the leftist views – the so-called “moscowphils”, who held a strong position among the intelligentsia and Greek Catholic clergy, and later turned into “sovietophils”. The article examines the leftist views of Ukrainian composers Stanisław Ludkiewicz, Mykoła Kołessa, Zynowij Łyśko, pianist Hala Lewicka, wife of the socialist activist Ivan Kruszelnicki.